Vitamin B5 Reduces Bacterial Growth via Regulating Innate Immunity and Adaptive Immunity in Mice Infected with Mycobacterium tuberculosis - He, Wenting; Hu, Shengfeng; Du, Xialin; Wen, Qian; Zhong, Xiao-Ping; Zhou, Xinying; Zhou, Chaoying; Xiong, Wenjing; Gao, Yuchi; Zhang, Shimeng; Wang, Ruining; Yang, Jiahui; et al. (Frontiers in Immunology, 2018)
The mechanisms by which vitamins regulate immunity and their effect as an adjuvant treatment for tuberculosis have gradually become very important research topics. Studies have found that vitamin B5 (VB5) can promote epithelial cells to express inflammatory cytokines. We aimed to examine the proinflammatory and anti-bacterial effect of VB5 in macrophages infected with Mycobacterium tuberculosis (MTB) strain H37Rv and the therapeutic potential of VB5 in vivo with tuberculosis. We investigated the activation of inflammatory signal molecules (NF-κB, AKT, JNK, ERK, and p38), the expression of two primary inflammatory cytokines (tumor necrosis factor and interleukin-6) and the bacterial burdens in H37Rv-infected macrophages stimulated with VB5 to explore the effect of VB5 on the inflammatory and anti-bacterial responses of macrophages. We further treated the H37Rv-infected mice with VB5 to explore VB5’s promotion of the clearance of H37Rv in the lungs and the effect of VB5 on regulating the percentage of inflammatory cells. Our data showed that VB5 enhanced the phagocytosis and inflammatory response in macrophages infected with H37Rv. Oral administration of VB5 decreased the number of colony-forming units of H37Rv in lungs of mice at 1, 2, and 4 weeks after infection. In addition, VB5 regulated the percentage of macrophages and promoted CD4+ T cells to express interferon-γ and interleukin-17; however, it had no effect on the percentage of polymorphonuclear neutrophils, CD4+ and CD8+ T cells. In conclusion, VB5 significantly inhibits the growth of MTB by regulating innate immunity and adaptive immunity.